Syntheses, Magnetic and Spectral Studies on the Coordination Compounds of the Polystyrene-anchored Thiazolidin-4-one - Dinesh Kumar; Amit Kumar (E-Journal of Chemistry)
The reaction between polystyrene 3-formylsalicylate and thiophene-2-carboxylic acid hydrazide in DMF in the presence of ethyl acetate results in the formation of polystyrene N-(2-carbamoylthienyl)-3'-carboxy-2'-hydroxybenzylideneimine (I). A benzene suspension of I reacts with mercaptoacetic acid and forms the polystyrene N-(2-carbamoylthienyl)-C-(3'-carboxy-2'-hydroxyphenyl) thiazolidin-4-one, PSCH2–LH2 (II). A DMF suspension of II reacts with Zn(II), Co(II), Cu(II), Zr(OH)2(IV) and MoO2(VI) ions and forms the corresponding polystyrene-anchored coordination compounds, [PSCH2–LZn(DMF)] (III), [PSCH2–LCo(DMF)3] (IV), [PSCH2–LHCu(OAc)] (V), [PSCH2–LH2Zr(OH)2(OAc)2] (VI) and [PSCH2–LHMoO2(acac)] (VII) respectively. The polystyrene-anchored coordination compounds have been characterized on the basis of elemental analyses, spectral (IR, reflectance, ESR) studies and magnetic susceptibility measurements. II acts as a neutral tridentate ONS donor ligand in VI, a monobasic bidentate OS donor ligand in VII, a monobasic tridentate ONS donor ligand in V and a dibasic tridentate ONO donor ligand in III and IV. The acetato groups behave as monodentate ligands in V and VI. A square-planar structure for V, a tetrahedral structure for III, an octahedral structure for IV and VII and a pentagonal-bipyramidal structure for VI are suggested.